Analisis Daya Saing Ekspor Biji Kakao Indonesia ke Kawasan ASEAN Periode 2003-2012 - Ika Permatasari, I Gusti Ayu; Rustariyuni, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 7, Juli 2015 (pp.746 - 872), 2015)
Cacao beans are one of Indonesia's main export commodity. This study aimed to analyze the strength of competitiveness and market share of Indonesian cocoa exports in the ASEAN region.. The analytical tool used is the Revealed Comparative Advantage (RCA) and Constant Market Share Analysis (CMSA). State comparison used is state of Malaysia and Singapore. RCA value of the average Indonesia 2003-2012 period amounted to 6.86 can be interpreted that the Indonesian cocoa beans have strong competitiveness in the ASEAN region. Malaysia and Singapore have RCA average value of 0.28 and 0.02 which states that the two countries still has strong competitiveness in the ASEAN region. CMSA claimed effect of Indonesia's competitiveness has a strong influence on the growth of Indonesian cocoa exports, Malaysia and Singapore. However, the low quality of Indonesian cocoa beans exported can be a threat to Indonesia, to the government's need to improve the quality of Indonesian cocoa beans.
Keywords: Competitiveness,Export,Indonesian Cocoa Beans,RCA,CMSA